Periodontal Status and Oral Health-Related Quality of Life among Elderly attending Kantipur Dental College, Kathmandu, Nepal - Khapung, Anju; Rao, G. Nagaraja; Shrestha, Sujita; Dhami, Bhageshwar (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
Background: In elderly, poor oral health in the form of tooth loss, dental caries, periodontal disease and oral cancer affects physical and psychological aspect of life. Health is not only absence of disease but also psychological and social well-being. Thus, the assessment of disease by clinical examination as well as measurement of psychosocial impacts associated with disease are equally important. Aim: To find the association between periodontal status and oral health-related quality of life among elderly attending Kantipur Dental College. Materials and Methods: A cross-sectional study was carried out among 184 elderly patients attending Kantipur Dental College by convenient sampling method. Oral health-related quality of life was assessed by GOHAI. Periodontal status was assessed by using CPI modified and Loss of attachment. Data was analysed with SPSS version 20. Results: Among 184 total participants (74 men, 110 women), the mean GOHAI score was 46.59+8.70. Of the total, 13% had high GOHAI score whereas 27% had moderate and 60% had low GOHAI score. Periodontal status of elderly population was found to be significantly associated with oral health-related quality of life (p<0.05). Conclusion: The findings of this study suggest a need to improve oral health care and knowledge for elderly group through preventive and curative public health measures.